2015
DOI: 10.3791/53288
|View full text |Cite
|
Sign up to set email alerts
|

An Endothelial Planar Cell Model for Imaging Immunological Synapse Dynamics

Abstract: Adaptive immunity is regulated by dynamic interactions between T cells and antigen presenting cells ('APCs') referred to as 'immunological synapses'. Within these intimate cell-cell interfaces discrete sub-cellular clusters of MHC/Ag-TCR, F-actin, adhesion and signaling molecules form and remodel rapidly. These dynamics are thought to be critical determinants of both the efficiency and quality of the immune responses that develop and therefore of protective versus pathologic immunity. Current understanding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…As a drawback, only those APC-T cell interfaces that were perpendicular to the plane of focus along the Z-axis could be properly analyzed (45). Since other experimental models that may facilitate image capture and analyses do not mimic the complex, irregular surface of an APC or a target cell, and may raise to non-physiological interactions in the IS (6063), we consider the experimental system used here appropriate to address some biological events occurring at the IS. In addition, with the use of the PKCδ C1-based U.DAG2 sensor, we have shown that upon synaptic activation, DAG species are produced that may recruit PKCδ at endomembranes including MVB.…”
Section: Discussionmentioning
confidence: 99%
“…As a drawback, only those APC-T cell interfaces that were perpendicular to the plane of focus along the Z-axis could be properly analyzed (45). Since other experimental models that may facilitate image capture and analyses do not mimic the complex, irregular surface of an APC or a target cell, and may raise to non-physiological interactions in the IS (6063), we consider the experimental system used here appropriate to address some biological events occurring at the IS. In addition, with the use of the PKCδ C1-based U.DAG2 sensor, we have shown that upon synaptic activation, DAG species are produced that may recruit PKCδ at endomembranes including MVB.…”
Section: Discussionmentioning
confidence: 99%
“…That finding and the detection of ACh in the plasma and blood of various animal species, including humans, along with the development of highly sensitive radioimmunoassays [21], led to investigations into the origin of ACh in the blood and its physiological function (see also the reviews [15,22,23]). VECs constitutively express major histocompatibility complex (MHC) I and II and a range of costimulatory molecules, including intercellular adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1), under the regulation of inflammatory cues (see a review by Carman and Martinelli [24]). VECs thus play an essential locally tuned role in the regulation of T cell migration and information exchange.…”
Section: Ach-mediated Interaction Of Vascular Endothelial Cells (Vecs) With T Cellsmentioning
confidence: 99%